Associations between sex, body mass index, and the individual microglial response in Alzheimer's disease. (31st December 2021) - Biechele, Gloria; Rauchmann, Boris‐Stephan; Janowitz, Daniel; Buerger, Katharina; Franzmeier, Nicolai; Weidinger, Endy; Guersel, Selim; Schuster, Sebastian; Finze, Anika; Harris, Stefanie; Schmitt, Julia; Beyer, Leonie; et al.
Abstract: Background: 18‐kDa translocator protein position‐emission‐tomography (TSPO‐PET) imaging emerged for in vivo assessment of neuroinflammation in preclinical and clinical research of Alzheimer's disease (AD). Higher TSPO‐PET binding as a surrogate of microglial activation in females has been reported for cognitively normal humans (HC), but sex effects have not yet been systematically evaluated in patients with AD. Thus, we aimed to investigate the impact of sex and the body mass index (BMI) on the relationship between β‐amyloid‐accumulation and microglial activation in AD. Method: Fifty‐six patients with AD (34 female; BMI 24.9±4.0; age 71.1±7.7 years; 100% Aβ‐positive; MMSE 20.9±5.5) and 13 Aβ‐negative HC (7 female; BMI 24.2±3.3; age 70.6±7.5 years; MMSE 29.0±1.0) underwent TSPO‐PET ( 18 F‐GE‐180) and β‐amyloid‐PET imaging (Aβ‐PET; 18 F‐flutemetamol). The brain was parcellated into 218 cortical regions and standardized‐uptake‐value‐ratios (SUVr, cerebellar reference) were calculated for TSPO‐ and Aβ‐PET. Per AD patient, the averaged regional increase of TSPO‐ and Aβ‐PET SUVr (z‐score) was calculated versus HC. We used the function between regional Aβ‐PET and TSPO‐PET SUVr to determine the Aβ‐plaque dependent microglial response (slope) and the Aβ‐plaque independent microglial response (intercept) at the single patient level (Figure 1). All PET read‐outs were compared between sexes and we tested for a moderation effect of sex on the association between BMI and microglial activation, controlled for age. Result: In AD the mean cortical TSPO‐PET z‐score of females (+0.69±0.72) was higher when compared to males (+0.30±0.73; p=0.048; Figure 2), whereas Aβ‐PET z‐scores were similar (female: +4.56±1.76; male: +4.44±2.08). The Aβ‐plaque independent microglial response was stronger in females with AD (intercept: +0.35±0.63) when compared to males (‐0.23±0.71; p=0.0024) whereas the Aβ‐plaque dependent microglial response was indifferent between sexes (Figure 2). BMI and the Aβ‐plaque independent microglial response were significantly associated in females (β=0.35, p=0.043) but not in males (β=‐0.02, p=0.940; BMI*sex interaction: F(3, 52) =4.77, p=0.0052; Figure 3). Conclusion: Females with AD comprise a higher Aβ‐plaque independent microglia response, whereas the microglial response to fibrillar Aβ is indifferent between sexes. BMI is positively associated with the Aβ‐plaque independent microglia response in females with AD but not in males, indicating that sex and BMI need to be considered when studying neuroinflammation in AD.